Method, system, and computer program product for visualizing data using partial hierarchies - Tesler, Joel D. (2000)
A method, system, and computer program product provides data visualization which optimizes visualization of and navigation through hierarchies. A partial hierarchy is generated and displayed. The partial hierarchy consists of a number levels at least equal to a predetermined depth and less than a total number of levels included in a corresponding complete hierarchy. Parent nodes in the bottom level of the partial hierarchy have segments of connection lines extending toward child nodes not included in the partial hierarchy. A user is permitted to mark selected nodes or locations in a displayed partial hierarchy. Partial hierarchies are generated and stored in a cache or generated on-the-fly. Each partial hierarchy ends at a progressively deeper level. An interpolator interpolates a partial hierarchy layout by interpolating corresponding nodes in two partial hierarchies. A hierarchy manager manages partial hierarchies in response to requests from a viewer to move a camera to camera positions. Partial hierarchies are fetched from the cache or the interpolator. A display then displays display views of fetched partial hierarchies corresponding to the camera positions. During free-form navigation, a hierarchy manager determines and maintain an orientation based on at least one reference object. During zooming, an angular orientation is maintained through successive partial hierarchies. Mapping is also provided between a three-dimensional 3D partial hierarchy and a two-dimensional 2D overview of a complete hierarchy.